Performance evaluation of Atomic Commit Protocols for mobile transactions. (21st August 2007) - Nouali-Taboudjemat, Nadia; Boukantar, Lynda; Drias, Habiba
The commitment of a distributed transaction is ensured with the use of an Atomic Commit Protocol (ACP). Due to their great importance for transaction systems, the recent advances in mobile computing development have renewed the interest in the ACPs for mobile transactions. We compare assets of mobile ACPs that have been simulated on the NS-DBsim platform integrating two simulation environments; the NS2 simulator and DBsim a distributed database simulator. NS-DBsim takes into account the various and fluctuant parameters of wireless and mobile systems. The comparison highlights performance indices and orientations to the design of ACPs in mobile wireless environments.